Preliminary landslides detection using optical fiber as sensor element - Riera, Bruno Henrique dos Santos [UNIFESP] (2022)
Landslides are natural events with severe socio-economic impacts in the world with expressive lives disappearing and losses. The climate changes are influencing the glaciers causing the melting quickly and consequently affecting the stability of mountains in some regions of the world. Currently, different technologies are being used to detect severe phenomena in nature (hurricanes, floods, earthquakes, typhoons, and landslides), thus assisting society and government entities (body firefighters, research institutes, natural disaster detection centers, among others) against natural disasters and loss of life. Those technologies work remotely detecting by either by optical data, which are image-processing techniques for mapping, characterization, and monitoring, or underground systems collecting temperature, pressure, humidity, water volume through sensors. The mentioned technologies present high costs of implementation and complex accessibility of installation in already urbanized areas. This study aims to validate a system in the laboratory for detecting landslides using optical fiber as a sensor element in areas susceptible to natural disasters to save lives. The principle of the Fiber Bragg Grating (FBG) will be the technique to be studied in the laboratory to detect, along with the optical fiber, where pressure and temperature disturbances are occurring. With the completion of the study, we will have (1) a Comprehensive theoretical foundation of natural disasters. (2) Socioeconomic consequences. (3) Panoramic overview of the technology employed in Brazil for monitoring landslides in the national center. (4) FBG and laser concepts. (5) Systematic literature review. (6) Cost survey comparing a hypothetical FGB topology with the technology employed by National Center for Monitoring and Natural Disaster Alerts (CEMADEN) in Brazil. (7) Outcomes from the workshop with the Federal University of São Paulo (UNIFESP), Technological Institute of Aeronautics (ITA), and CEMADEN. (8) Evidenced results in a laboratory operating and measuring the lasers, photo-detector characterization, splicing and connecting the fiber, transmission and reception spectrum measures, and FBG strain measures. The technique proposed using FBG inscriptions along with the optical fiber and positioned at strategic underground points will be periodically interrogated to allow constant monitoring in real-time and enable the Civil Defense to issue evacuation alerts on time, minimizing damage and mainly saving lives.